PENGARUH BRAND IMAGE, KUALITAS, PERSEPSI HARGA DAN VARIASI PRODUK TERHADAP MINAT BELI KONSUMEN SARUNG GAJAH DUDUK DI KABUPATEN PEKALONGAN - Wijayasari, Nilla; Mahfudz, Mahfudz (Diponegoro Journal of Management, 2018)
The development of textile industry and fashion in Indonesia is rapidly increasing which caused fierce competition between businesses. This can be seen from the decline in sales sarong Gajah Duduk. Sarong Gajah Duduk is a pre-eminent sarong brand of PT.Pismatex pekalongan.Sarong Gajah Duduk it is first time marketed in 1972. This research was conducted to  analyze  the  effect  of  brand  image,  quality,  price  perpection  and  product  variation  on purchase intention of Sarong Gajah Duduk  product located in Pekalongan.Data collection technique used in this study are questionnaire. Sampling technique used is purposive sampling technique by convenience sampling which is choosing respondents who by chance met the researcher. Respondents of this research as many as 100 people. To analyze the impact of independent variables on dependent variable, multiple linier regression analysis is used.The result of this study showed that brand image have a negative effect on purchase intention (first hypothesis rejecte. The second hypothesis which state that quality have a positive impact on purchase intention is accepted as well. The third hypothesis which state that price perpection have a positive effect on purchase intention is accepted and the fourth hypothesis which state that product variation have a positive effect on purchase intention is accepted. The coefficient of determination test result stated that all four independent variables have an 40,7% on purchase intention.